If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + a)(x + b) = 0 Reorder the terms: (a + x)(x + b) = 0 Reorder the terms: (a + x)(b + x) = 0 Multiply (a + x) * (b + x) (a(b + x) + x(b + x)) = 0 ((b * a + x * a) + x(b + x)) = 0 ((ab + ax) + x(b + x)) = 0 (ab + ax + (b * x + x * x)) = 0 (ab + ax + (bx + x2)) = 0 (ab + ax + bx + x2) = 0 Solving ab + ax + bx + x2 = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1bx' to each side of the equation. ab + ax + bx + -1bx + x2 = 0 + -1bx Combine like terms: bx + -1bx = 0 ab + ax + 0 + x2 = 0 + -1bx ab + ax + x2 = 0 + -1bx Remove the zero: ab + ax + x2 = -1bx Add '-1x2' to each side of the equation. ab + ax + x2 + -1x2 = -1bx + -1x2 Combine like terms: x2 + -1x2 = 0 ab + ax + 0 = -1bx + -1x2 ab + ax = -1bx + -1x2 Reorder the terms: ab + ax + bx + x2 = -1bx + bx + -1x2 + x2 Combine like terms: -1bx + bx = 0 ab + ax + bx + x2 = 0 + -1x2 + x2 ab + ax + bx + x2 = -1x2 + x2 Combine like terms: -1x2 + x2 = 0 ab + ax + bx + x2 = 0 The solution to this equation could not be determined.
| 12+1.65*3=16.95 | | 2q-4=5q+5 | | -56+(-30)= | | ap-p+2a+p+ap= | | 15x^2+69x+36=0 | | w+3*w=70 | | -1/4a=3/8 | | X-2=2(4-x) | | -6y+14+4y=0 | | 11r+r^2+18=0 | | 6p-5q= | | 5+r=19 | | v^2+3v=0 | | 2x^2+3x+1=3x^2-3x | | 2.6x+2-6.6x=10 | | .75(2x-8)=4 | | 10x^2+46x-20=0 | | 2(4x-4.8)=5x-9.6 | | x(x+6)=27 | | 5z^2=95 | | 2.3x-22=1.5x+6 | | 2x/3-8=x+7 | | 12x+6=9x+34 | | 9x+4.88=5x+10 | | 2w^2+19w+42=0 | | x^2+20x+14=0 | | 1.9+0.2x=0.1 | | 709-162= | | 6p-8-5p=2 | | Ab-b+2a+b+ab= | | 21x^2-2x-3=0 | | 20x+7y=7 |